Solusi Gaya Kepemimpinan Pendidikan Islam di Era Modern - Hoerul Ansori (STAI Terpadu Yogyakarta, 2019)
Educational leadership in the modern era like today, there are still many who crave good leadership and can create a conducive environment between superiors as the head and the person in charge, along with subordinates as executors of the task. To create a good leadership, one must have a leader who is a master and expert in the science of leadership, so that the institution being led can succeed by achieving the goals that were targeted from the start. To present a good educational leadership and create a conducive atmosphere in the modern era as it is today, the things that must be done are (1) to impose a concept of community-based education leadership, (2) to preside over character-based educational leadershi, and (3) Emotional Intelligence in Conflict Control. In order to create an atmosphere of educational leadership that is ideal for the modern era at this time.